Nutrient metabolism and ingestive behavior of goats fed diets containing palm tree fruit - Garcez, Bruno; Alves, Arnaud; de Oliveira, Maria Elizabete; Moreira Filho, Miguel; Azevêdo, Danielle Maria; Lacerda, Marlúcia (Revista Ciência Agronômica, 2020)
The objective was to evaluate the nutrient metabolism and ingestive behavior of goats fed diets containing fruits of Carnauba and Tucum palm trees, abundant in the Northeast region with fruiting in the dry season and use as alternative food for ruminants. For this end, 21 goats fed three diets, one control and two with carnauba or tucum fruits, in a completely randomized design. We determined nutrient intake through total collection of leftovers, faces and urine, as well as energy and nitrogen balance. Ingestive behavior was assessed by visual observations every 5 min for 24 h. There was a reduction in dry matter intake of 0.183 and 0.223 kg/day for diets containing tucum and carnauba fruits, respectively. The intake of digestible protein (78.04 gDP/day) and metabolizable energy (2.51 McalME/day) of the diet containing tucum fruits met the nutritional requirements of the animals, besides resulting in nitrogen balance above 60% and increase of 0.57 Mcal/kgDM of digestible energy of the diets. Diets containing fruits of carnauba required a longer rumination (453.65 min/day), associated with the higher fiber content in their composition. The inclusion of carnauba and tucum fruits in diets composed of corn, soybean and Tifton 85 hay for growing goats promotes a reduction in dry matter intake due to the low quality of the fiber of these fruits. However, the diets containing tucum fruits met the nutritional requirements of goats regarding digestible protein and metabolizable energy, suggesting the use of this alternative food for this category.